Clinical outcomes of non–small-cell lung cancer patients with BRAF mutations: results from the French Cooperative Thoracic Intergroup biomarkers France study. (July 2019) - Couraud, Sébastien; Barlesi, Fabrice; Fontaine-Deraluelle, Clara; Debieuvre, Didier; Merlio, Jean-Philippe; Moreau, Lionel; Beau-Faller, Michèle; Veillon, Rémi; Mosser, Jean; Al Freijat, Faraj; Bringuier, Pierre-Paul; Léna, Hervé; et al.
Abstract: Introduction: Patients with stage IV non–small-cell lung cancer (NSCLC) and BRAF V600 mutations may benefit from targeted therapies. Chemotherapy outcomes are little known in this population. Methods: The French Cooperative Thoracic Intergroup (IFCT) Biomarkers France study was a national prospective cohort study aiming to describe the molecular characteristics and clinical outcome of all consecutive NSCLC patients (N = 17, 664) screened for molecular alterations. We used this data set to set up a case–control analysis. Cases had stage IV BRAF- mutated ( BRAF -MT) NSCLC, whereas controls had NSCLC that was wild-type for EGFR, KRAS, HER2, BRAF, PIK3CA and ALK . Each case was matched for sex, age at diagnosis and smoking status to two controls randomly selected. Results: Overall, 83 cases with BRAF mutant disease (66.3% V600E) were matched to 166 controls. Five cases received tyrosine kinase inhibition in the first-line and 16 in the second-line. All others were treated with standard chemotherapy. There was no significant difference in first-line and second-line progression-free survival (PFS) between the groups, as well as in the disease control rate, BRAF mutation was not found to be prognostic of overall survival. We found no significant difference in outcome between the treatment types used in first-line or second-line in patients with BRAF -MT disease compared with controls nor between BRAF V600E or non-V600E compared with controls. Conclusions: BRAF mutation is not a strong prognostic factor in NSCLC. Although taxan-based therapy shows poorest PFS in first-line, no chemotherapy regimen was associated with prognosis. Highlights: Large cohort of patients with BRAF -mutant non–small-cell lung cancer (NSCLC). No clear evidence that BRAF status influences progression-free survival (PFS) or overall survival in patients treated with chemotherapy. Taxans were associated with poorest PFS in first-line in patients with BRAF mutant disease. No significant difference in outcome between BRAF V600E or non-V600E compared with wild type controls. Results re-enforce the strong place of targeted therapies in patients with BRAF-mutant NSCLC.